2015
DOI: 10.1002/pssr.201510394
|View full text |Cite
|
Sign up to set email alerts
|

Photonic nanostructures for advanced light trapping in silicon solar cells: the impact of etching on the material electronic quality

Abstract: Dry plasma etching, commonly used by the Photonics community as the etching technique for the fabrication of photonic nanostructures, could be a source of device performance limitations when used in the frame of silicon photovoltaics. So far, the lack of silicon solar cells with state‐of‐the‐art efficiencies utilizing nanophotonic concepts shows how challenging their integration is, owing to the trade‐off between optical and electrical properties. In this study we show that dry plasma etching results in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
2
6
1
Order By: Relevance
“…This means that the plasma treatment of the silicon surface can destroy the crystal order in the subsurface region, leading to dangling bonds formation. In contrast, in a previous study, DLTS spectra also exhibited the responses from the deep center at high temperatures contrary to our experiments. Therefore, during the cryogenic ICP process, less degradation of silicon occurs due to lower ion bombardment.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…This means that the plasma treatment of the silicon surface can destroy the crystal order in the subsurface region, leading to dangling bonds formation. In contrast, in a previous study, DLTS spectra also exhibited the responses from the deep center at high temperatures contrary to our experiments. Therefore, during the cryogenic ICP process, less degradation of silicon occurs due to lower ion bombardment.…”
Section: Resultscontrasting
confidence: 99%
“…It is correlated well with our DLTS spectra obtained for n-Si etched in SF 6 /O 2 gas mixture. The DLTS spectra in our study (Figure 7b) and in the study by Trompoukis et al [42] are similar, suggesting that the observed defect is related to the P b type. This means that the plasma treatment of the silicon surface can destroy the crystal order in the subsurface region, leading to dangling bonds formation.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations